2006
DOI: 10.1002/em.20265
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic activities of crude extracts from Acacia salicina leaves

Abstract: For centuries, plants have been used in traditional medicines and there has been recent interest in the chemopreventive properties of compounds derived from plants. In the present study, we investigated the effects of extracts of Acacia salicina leaves on the genotoxicity of benzo[a]pyrene (B(a)P) and nifuroxazide in the SOS Chromotest. Aqueous, total oligomers flavonoids (TOF)-enriched, petroleum ether, chloroform, ethyl acetate, and methanol extracts were prepared from powdered Acacia leaves, and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…The weak cytotoxic activities exhibited by some R. alaternus extracts against the two cell lines indicated that the compounds present in the extracts are non cytotoxic. However, since reactive oxygen radicals play an important role in carcinogenesis (Lee et al, 1998, Abdelwahed et al, 2007Bouhlel et al, 2007;Ben Mansour et al, 2007), it is possible to suggest that the presence of antioxidants in the active R. alaternus extracts (Chevolleau et al, 1992;Ben Ammar et al, 2005) may play some role in reducing cell number. High antibacterial and high cytotoxic activities were observed in the A 2 fraction compared to the aqueous extract A.…”
Section: Results Of These Experiments Shown Inmentioning
confidence: 99%
“…The weak cytotoxic activities exhibited by some R. alaternus extracts against the two cell lines indicated that the compounds present in the extracts are non cytotoxic. However, since reactive oxygen radicals play an important role in carcinogenesis (Lee et al, 1998, Abdelwahed et al, 2007Bouhlel et al, 2007;Ben Mansour et al, 2007), it is possible to suggest that the presence of antioxidants in the active R. alaternus extracts (Chevolleau et al, 1992;Ben Ammar et al, 2005) may play some role in reducing cell number. High antibacterial and high cytotoxic activities were observed in the A 2 fraction compared to the aqueous extract A.…”
Section: Results Of These Experiments Shown Inmentioning
confidence: 99%
“…As far as, hexane extract prepared from Acacia salicina leaves has been revealed in previous works as enriched by sterols [25]; these sterols were responsible for antioxidant activity, that has been observed in that work. We have opted in our study for the determination of the ability of this extract, for reducing the formation of reactive oxygen species (ROS) using the enzymatic system cholesterol/cholesterol oxidase.…”
Section: Introductionmentioning
confidence: 82%
“…However, a comparative study of the same species, collected from two Tunisian regions (Monastir and Médenine), showed that the antioxidant activity is more extensive inside the plant samples collected from Medenine compared to those of Monastir. This result could be explained by the richness of phytosterols in Médenine plants, to which we have attributed the biological activities [25,28]. Furthermore, we have evaluated the ability of a hexane extract, prepared from fresh leaves of A. salicina on decreasing H 2 O 2 rate.…”
Section: Antioxidant Activities Of Phytosterol and Their Therapeutic mentioning
confidence: 91%
See 1 more Smart Citation
“…Phenolic acids have been shown to be anti-oxidant and it is a potent antagonist of the mutagenicity of polycyclic aromatic hydrocarbons (PAHs) such as T benzo(a)pyrene (BaP) (Mansour et al, 2007). Benzo(a)pyrene is a semi-volatile, lipophilic, high molecular weight compound that belongs to the polycyclic aromatic hydrocarbon (PAH) family.…”
Section: Zoology Department College Ofmentioning
confidence: 99%